Differential Ability of Bovine Antimicrobial Cathelicidins to Mediate Nucleic Acid Sensing by Epithelial Cells - Baumann, Arnaud; Kiener, Mirjam Susanna; Haigh, Brendan; Perreten, Vincent; Summerfield, Artur (Frontiers in Immunology, 2017)
Cathelicidins encompass a family of cationic peptides characterized by antimicrobial activity and other functions, such as the ability to enhance the sensing of nucleic acids by the innate immune system. The present study aimed to investigate the ability of the bovine cathelicidins Indolicidin, Bac1, Bac5, BMAP-27, BMAP-28 and BMAP-34 to inhibit the growth of bacteria and to enhance the sensing of nucleic acid by the host’s immune system. BMAP-27 was the most effective at killing Staphylococcus aureus, Streptococcus uberis and Escherichia coli, and this was dependent on its amphipathic structure and cationic charge. Although most cathelicidins possessed DNA complexing activity, only the alpha-helical BMAP cathelicidins and the cysteine-rich disulfide-bridged Bac1, were able to enhance the sensing of nucleic acids by primary epithelial cells. We also compared these responses with those mediated by neutrophils. Activation of neutrophils with phorbol myristate acetate resulted in degranulation and release of cathelicidins as well as bactericidal activity in the supernatants. However, only supernatants from unstimulated neutrophils were able to promote nucleic acid sensing in epithelial cells. Collectively, the present data supports a role for certain bovine cathelicidins in helping the innate immune system to sense nucleic acids. The latter effect is observed at concentrations clearly below those required for direct antimicrobial functions. These findings are relevant in development of future strategies to promote protection at mucosal surfaces against pathogen invasion.